PENGARUH PERTUMBUHAN EKONOMI DAN TINGKAT PENDIDIKAN TERHADAP DISPARITAS PENDAPATAN DI WILAYAH GERBANGKERTOSUSILA - Nuraini, Emi (UNIVERSITAS NEGERI SURABAYA, 2017)
This study aims to analyze the influence of economic growth and educational level towards income disparity on Gerbangkertosusila region either partially or simultaneously. Gerbangkertosusila in 2003-2012 becomes the subject of this research. In addition, the research uses sampling saturated and regression models for panel data analysis to achieve the aims of this study.The results of this study showed that (1) partially economic growth significantly does not influence the income disparity in Gerbangkertosusila region. The invention indicates that economic growth can not be distributed evenly. (2) The level of education have a significant effect on the income disparity of Gerbangkertosusila. The total population of high educated people in Surabaya is higher than others. So, Surabaya has higher income disparity too. (3) While simultaneously, economic growth and education level significanly influence the income disparity in Gerbangkertosusila region. The findings showed that Surabaya has different income disparity. It is because Surabaya as a capital area than other regencies as supporting area. So there is a high gap between capital and supporting area. The government is expected to be able to increase the industrial sectors output, services and capital goods so that high economic growth can be achieved and more attention to the education sector, especially in the central areas of growth